FLOATING STATE: PERGULATAN NEGARA PASCA-KOLONIAL DAN REZIM NEOLIBERAL STUDI ATAS INDONESIA PASCA ORDE BARU - , Adde Marup Wirasenja, SIP.; , Prof. Dr. Purwo Santoso, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Two points are discussed in this research. Firstly, It argues that the process of market transformation is not a neutral in essence. It is far from the theoretical construction of neoliberal scholars who believe that market can be run harmouniously â bring about benefit impacts to all man kind - throught the logic of invisible hand. Indeed, this research believe that behaviours and interests of the market have been defined and constructed by the structure of world capitalists system designed by the dominant actors. âThe visible handâ of global capitalism has constructed not only the interaction of states in economic realm but also in the format of the state in post-colonial world like Indonesia. Dramatically, in post-colonial state they have been functionced as âdouble bladeâ, being put side by side to support and protect the ideas of global market expansion, which eventually make states to become the new motherland of late capitalism. Secondly, by using contructivist thought from Alexander Wendt, this research focuses on the structural consequences of post-colonial states in democratization era. Far from the imagination of social-contract sholars that inspiring the development and the successed of Western Liberal Democracy, the market construction within the system of global capitalism has blocked the processes in post-colonial states, particularly in the states which are highly depended to the system. They fail to synthesize the substance of democracy with the dynamic of social, political, and culture configuration in domestic level. As a consequence, post-colonial state as political aspiration and institution have been downgraded by market and subsumed into the world capitalism system. Postcolonial state aspiration only happends within domestic political structure, while states as a political agent merely to be functioned as âmarket apparatusâ which hold the sustainability global capitalists regime.